KETERBUKAAN ORGANISASI : TANGTANGAN DALAM MENGHADAPI PERSAINGAN - Rullijanto DP (Universitas Trisakti, 2001)
The competition that happens these days not only limited to competition among national companies but also against foreign companies, the competition Affect Company's wills behavior. Competition creates, uncertainty, without a high a company may face a big problem in this new global arena quality of human resources.